Diseño, síntesis y caracterización de posibles quimiosensores de metales basados en triazinas para uso en plataformas microfluídicas basadas en papel (2020)
Overexposure to transition metals can be linked to a multitude of diseases such as cancer, diabetes, atherosclerosis, Alzheimer's, Parkinson's and chronic inflammation. At present there are several analytical methods capable of detecting metals at the ultra-trace level that can be used in various arrays. However, the costs per analysis performed in any of these equipments is extremely high, not counting the cost and time necessary for the collection and preparation of the samples, which means that only certain entities with sufficient economic and human capital can perform these types of analisys. Microfluidics is the discipline that studies the behavior of fluids at volumes on the scale from [mi]L to [eta]L, this study has led to the creation of cheap chemical analysis platforms, easy to manufacture and operate, of these the most accessible is paper, which when used in conjunction with fluorescent chemosensors can give a quantifiable response with little spectral interference. Due to this, the synthesis of new molecules derived of cyanuric chloride to be used as chemosensors cabpable of detecting metals in paper-based microfluidic applications is considered necessary .--Taken from the Degree Document Format.